1990
DOI: 10.1177/106002809002400316
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine: An Immunomodulator

Abstract: Suppressor T lymphocytes possess histamine2 (H2) receptors and contribute significantly to the function of the immune system. Experimentally, cimetidine, an H2-receptor antagonist, has been shown to enhance a variety of immunologic functions both in vivo and in vitro because of its inhibitory effects on suppressor-cell function. Successful tumor immunotherapy, as well as some protection from infection, has been reported in experimental animals. Patients receiving cimetidine have been shown to exhibit enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Kumar, A. reported that suppressive T lymphocytes possess histamine2 (H2) receptors and contribute significantly to the function of immune system. 11 Jutel M et al proposed that histamine, through its H2 receptor, positively interferes with the peripheral antigen tolerance that is induced by regulatory T cells via several pathways. 33 However, it is uncertain whether histamine is also involved in CIM-stimulated Foxp3 reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar, A. reported that suppressive T lymphocytes possess histamine2 (H2) receptors and contribute significantly to the function of immune system. 11 Jutel M et al proposed that histamine, through its H2 receptor, positively interferes with the peripheral antigen tolerance that is induced by regulatory T cells via several pathways. 33 However, it is uncertain whether histamine is also involved in CIM-stimulated Foxp3 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Early studies had shown that CIM is capable of inhibiting suppressor cell effector function 7 and expansion 8 and that regulatory T cells possess the H2 receptor. [9][10][11] Experimentally, CIM has been shown to enhance a variety of immunologic functions both in vivo and in vitro, including decrease in the relative abundance or function of Treg cells in several studies. [12][13][14] Indeed, Wang J et al 14 reported that the use of CIM as a vaccine adjuvant in mice could induce expression of pro-inflammatory cytokines such as IL-6 and IL-12 and down-regulate expression of anti-inflammatory cytokines, including IL-10 and TGF-b.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism by which cimetidine may exert an anticancer effect remains uncertain. cimetidine is thought to exert its effect by blocking high peritumoral concentrations of histamine and increasing systemic immunoreactivity via H 2 receptor antagonism of circulating T suppressor cells or maintenance of natural killer cell activity (19)(20)(21). However, Rajendra et al (22) have demonstrated that cimetidine has a direct antiproliferative effect in the absence of histamine type 2 receptors and the induction of apoptosis.…”
Section: Cimetidine Inhibits the Growth Of Transplantable Tumorsmentioning
confidence: 99%
“…Several studies have suggested various mechanisms underlying the beneficial effect of cimetidine on cancer patients, such as the following: (i) reversal of the pharmacological activity of histamine, tumour growth promoter by blocking histamine receptors on cancer cells Reynolds et al, 1996) or affecting histamine metabolism (Garcia-Caballero et al, 1994); (ii) acting as an antioxidant, thus inhibiting tumour growth (Kimura et al, 1986) and (iii) augmentation of anticancer immune reactivity through receptor antagonism of circulatory suppressor T cells (Kumar, 1990), prevention of postoperative alterations of lymphocyte subpopulations (Hansbrough et al, 1986), or by maintenance of natural killer cell activity (Katoh et al, 1996). In our study, we found that cimetidine could block the expression of E-selectin on the surface of human umbilical vein endothelial cells, thus blocking the tumour cell adhesion to endothelium and preventing the liver metastasis in nude mice model (Kobayashi et al, 2000).…”
mentioning
confidence: 99%